HUBUNGAN ANTARA KONSEP DIRI DENGAN EFIKASI DIRI DALAM MEMECAHKAN MASALAH MELALUI KONSELING INDIVIDU DI SMK HIDAYAH SEMARANG - Yolanda Puspita Dewi; Heru Mugiarso (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2020)
This study aims to determine the relationship between self-concept and self-efficacy in solving problems through individual counseling at SMK Hidayah Semarang. The problem that underlies this research is that self-efficacy in solving problems in students is still in the low category. On the other hand, students are less open because they are less confident in their abilities when conducting individual counseling activities. This research is a type of correlational quantitative research. Sampling uses purposive sampling and simple random sampling. The sample in this study amounted to 83 students spread across all classes at SMK Hidayah Semarang. Measuring instruments used are the scale of self-concept and self-efficacy scale in solving problems. Analysis of the data used in the hypothesis test is a simple correlation test. The results showed that with self-efficacy in solving problems that are classified as high and have a positive and significant relationship between these variables. correlation results obtained by 0.580 with a significance of 0,000 or <0.05. From these results it can be understood that the higher the student's self-concept, the higher the self-efficacy in solving students' problems. With this research it is beneficial for BK teachers to provide innovation when conducting individual counseling services.